Écrire l’histoire d’une faide dans l’Islande du XIIIe siècle. Quelques remarques sur la Saga des Svínfellingar - Grégory Cattaneo (Tabularia)
This study is based on two purposes. First, it analyses the mechanism of a feud in an area of Eastern Iceland in the middle of the 13th century. Then it demonstrates the value of a contemporary saga as a historical source. The feud between the local elites appears in two written sources: the Icelandic Annals and the Saga of the Men of Svínafell (Svínfellinga saga). After a careful inspection of the sources of this feud, one can observe the importance of the saga testimony. The coalitions between the elite and the limitation of violence are analysed as a fundamental aspect of the feuding game. The process of conflict resolution and its social stakes are reconstituted through a meticulous study of the mediation. When it is relevant, one establishes a parallel between this feuding system and other examples, taken from other feuding societies, in Saga Age Iceland and in Feudal France.